Hereditariedade da cor das vagens de Phaseolus vulgaris L. - Lam Sánchez, Alfredo; Vieira, Clibas (Revista Ceres, 2024)
In the present genetic study, five varieties of dry beans were used: Préto-146 and Prêto-209, both with dark purple pods and violet flowers; Pardo-90, with red pods and pink flowers; Roxao, with red pods and white flowers; and Manteigao-Fésco-11, with yellow pods and White flowers. The pod colors were observed immediately before they began to ripen when the plants were 70 to 80 days old. Thus, Manteigão- Fôsco-ll is not considered a wax bean type since its pods are green and only change to yellow at maturity. From crossesbetween these varieties, the segregation of pod color and flower color was studied in the Fp Fp, and F3 generation. It was found that gene YV, which governs the violet flower color, modifies the action ofa gene for red pod color, here designatedª because of its similarity to the pod color gene described by LAMPRECHT (1951). The genotypes Ro-V- produce plants with dark purple pods and violet flowers , while the genotypes roroV- produce plants having yellow pods with violet stripes and violet flowers. The alleles for flower color, v for white and y12€ for pink, do not affect pod color . Consequently, v or vlãe together with Ro produces red pods and with ro, yellow pods.